Pengaruh Teknik Sosiodrama untuk Meningkatkan Keterampilan Komunikasi Interpersonal Siswa Laki-Laki Kelas SMK Ar-Rahman Misriadi Langkat - Khairina Ulfa Syaimi (Universitas PGRI SUMATERA BARAT, 2019)
This research is intended to observe the effect of through sociodrama technique in improving students’ interpersonal communication skill at the tenth-grade students of SMK Ar-Rahman Misriadi Langkat. In the research methodology, the writer used quasi-experimental design, focusing on non- equivalent control group design. In addition, to decide the sample of the research the writer used non-probability sampling technique in the form of purposive sampling technique. There were twenty four male students who had been chosen as the research sample.The sample chosen was classified based on the interpersonal communication skill in the lower rate. Moreover, the instrument used to decide the sample was the instrument of interpersonal communication skill which provided four options on a Likert scale. The technique of analysis was carried out by using descriptive statistics which provided empirical mean to know the average scores between the pre-test and the posttest in the experimental group and controlled group respectively. The result showed that the score of Asymp. Sig were 0.000 which meant that the interpersonal communication skill of the male students Sig < 0.05. It can be concluded that the high number of increasing of interpersonal communication skill was experienced by the male students in the experimental group than in the controlled group. Therefore, the result of this research was used to improve the interpersonal communication skill of the tenth- grade male students at SMK Ar-Rahman Misriadi Langkat.